The perceived impact of policy change on leadership and management : a case study of a Namibian school - Moelanjane, Porgarius Porgacy Rukee (Rhodes University, Faculty of Education, Department of Education, 2005)
The transformation of education has been central to the programme of the first democratically elected government in Namibia, both because of the democratic demands for equality, equity and access, and as a means towards the wider transformation of Namibian community. The study provides a brief history of the pre- and post-independence education policy environment in Namibia with regard to how management and leadership of schools gave rise to opportunities for the development of democratic participation. Adopting an interpretive approach, the study examines several key stakeholders' perceptions of the impact of transformation initiatives on their leadership and management thinking and practice. The sample comprised four teachers, a principal, a director, a school board member, two learners and a hostel matron. The findings reveal that, in order to create a democratic school community, the stakeholders' role is largely a matter of opposing and transcending the contradictions, inadequacies and limitations inherent in the educational ideas, policies and practices caused by the previous Apartheid education system. There is a reasonable amount of success in the implementation process of democratic leadership and management of schools. The findings further highlight contradictory tendencies, in that the Ministry of Basic Education Sports and Culture established a uniform system of education but also entertained the principle of decentralised governance through the introduction of school based management practice incorporating the main stakeholders at local level. The data confirms a communication gap between stakeholders, lack of adequate education and training in participatory management and leadership for learners, parents, teachers and school boards, and insufficient support from the national and the regional authorities. The study concludes with some specific recommendations that might strengthen stakeholders' sense of their participation in democratic practices for longer-term cost effective implementation to occur. This is supported by the belief that education policy change only becomes a reality once understood, owned and appreciated at local level.
Keywords: School management and organization -- Namibia -- Case studies; Educational leadership -- Namibia -- Case studies; Educational change -- Namibia -- Case studies; Education and state -- Namibia -- Case studies